Analysis of E-technology Support, E-digital Competence and E-work procedures on the Performance of Employees of PosIND Kediri branch - Oktaviana, Nita; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to understand how digital technology support, digital skills, and electronic work procedures affect employee performance at PosIND Kediri. Design/Methode/approach : This research uses a quantitative approach by collecting data through interviews and questionnaires. Data analysis includes validity test, reliability test, multiple linear regression, classical assumption test, and t test and F test using SPSS version 25.0. Research Finding : The results showed that the regression model obtained was Y = 1.242 + 0.064X1 + 0.285X2 + 0.598X3, with a constant value of 1.242. This means that without changes in the independent variables, employee performance remains at 1.242. The regression coefficient shows that e-technology support, e-digital competence, and e-work procedures contribute positively to improving employee performance by 0.064, 0.285, and 0.598, respectively. With a coefficient of determination of 0.752, it can be concluded that the three variables affect employee performance by 75.2%, while the remaining 24.8% is influenced by other factors not included in this study. Theoretical contribution/originality : This study reinforces the theory that proper technological support, competence, and work procedures significantly influence performance improvement. Practitione/policy implication : This research provides guidance for posIND to focus on technological and procedural development to optimize employee performance. Research limitation : This study is limited to a specific sector, making the results not broadly generalizable. Future studies are recommended to expand the sector coverage and include other relevant variables.